The organization of subglacial drainage during the demise of the Finnish Lake District Ice Lobe - Hepburn, Adam J.; Dow, Christine F.; Ojala, Antti; Mäkinen, Joni; Ahokangas, Elina; Hovikoski, Jussi; Palmu, Jukka-Pekka; Kajuutti, Kari (Copernicus GmbH, 2025)
Unknown basal characteristics limit our ability to simulate the subglacial hydrology of rapidly melting contemporary ice sheets. Sediment-based landforms generated beneath Late Pleistocene ice sheets, together with detailed digital elevation models, offer a valuable means of testing basal hydrology models, which describe the flow and dynamics of water in the subglacial system. However, to date no work has evaluated how well process-based subglacial hydrology models represent the hypothesized conditions associated with glaciofluvial landform formation in the palaeo setting. Previous work comparing model output to geomorphological evidence has typically done so using models that do not resolve subglacial processes and instead express likely subglacial water pathways. Here, we explore the ability of the Glacier Drainage System model (GlaDS), a process-based subglacial hydrology model, to represent the genesis conditions associated with a specific glaciofluvial landform termed "murtoos". Distinctive triangular landforms found throughout Finland and Sweden, murtoos are hypothesized to form 40-60 km from the former Fennoscandian Ice Sheet margin within a "semi-distributed" system at the onset of channelized drainage in small cavities where water pressure is equal to or exceeds ice overburden pressure. Concentrating within a specific ice lobe of the former Fennoscandian Ice Sheet and using digital elevation models with a simulated former ice surface geometry, we forced GlaDS with transient surface melt and explored the sensitivity of our model outcomes to parameter decisions such as the system conductivity and bed topography. Our model outputs closely match the general spacing, direction, and complexity of eskers and mapped assemblages of features related to subglacial drainage in "meltwater routes". Many of the predictions for murtoo formation are produced by the model, including the location of water pressure equal to ice overburden, the onset of channelized drainage, the transition in drainage modes, and importantly the seasonal sequence of drainage conditions inferred from murtoo sedimentology. These conclusions are largely robust to a range of parameter decisions, and we explore seasonal and inter-annual drainage behaviour associated with murtoo zones and meltwater pathways. Our results demonstrate that examining palaeo basal topography alongside subglacial hydrology model outputs holds promise for the mutually beneficial analyses of palaeo and contemporary ice sheets to assess the controls of hydrology on ice dynamics and subglacial landform evolution.